2019
DOI: 10.1097/pas.0000000000001386
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic Patterns and the Correlation With MYD88 L265P, CD79B Mutations in Primary Adrenal Diffuse Large B-Cell Lymphoma

Abstract: Primary adrenal diffuse large B-cell lymphoma (PA-DLBCL) is a rare subtype of extranodal DLBCL. Because of the rarity of this disease, its morphologic and genetic features are not comprehensively studied. Here, we systematically reviewed the clinicopathologic features of 42 cases of PA-DLBCL from our institution and investigated the frequency of MYD88 L265P and CD79B (exon 5) mutation in 29 eligible cases using Sanger sequencing. Clinically, PA-DLBCL was predominant in elderly male patients with advanced clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 44 publications
1
12
0
1
Order By: Relevance
“…Therefore, biphasic type suggests MYD88 L265P and CD79B double mutations, which was also observed in primary breast DLBCL. 12 …”
Section: Clinical Presentationmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, biphasic type suggests MYD88 L265P and CD79B double mutations, which was also observed in primary breast DLBCL. 12 …”
Section: Clinical Presentationmentioning
confidence: 99%
“…Patients with RS-like cells PA-DLBCL were more likely to involve CNS and the CNS-directed prophylactic interventions should be used in conjunction with initial therapy. 12 …”
Section: Outcome and Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Antikörper gegen folgende Antigene wurden verwendet: CD34, SMA ( smooth muscle actin), EMA ( epithelial membrane antigen ), S100‐Protein, Desmin, CD10, Cytokeratin und Ki‐67 (Tabelle S1, Online‐Supplement ). Der Ki‐67‐Index wurde in drei HPF gemessen (× 400) und anschließend ein Mittelwert berechnet [15].…”
Section: Immunhistochemieunclassified
“…MYD88 L265P is pathogenic, occurring at significant frequencies in hematologic malignancies such as chronic lymphocytic leukemia, marginal zone lymphomas of the ocular adnexa, primary central nervous system large B-cell lymphomas and multiple myeloma amongst numerous others [46,[48][49][50][51][52][53]. In three separate studies, L265P was found in over 90% of patients with lymphoplasmacytic lymphoma (LPL) and from 86-100% of patients with related Waldenström macroglobulinemia (WM) [54][55][56].…”
Section: Myd88 L265pmentioning
confidence: 99%